Information ecological imbalance and information intervention policies in digital ecosystems - Zhu, Dengya; Wang, H.; Chang, Elizabeth (IEEE Industrial Electronics Society, 2009)
This article explores ecological imbalance in digital ecology environment. With the dramatic growth of digital information in the world, organizations, in an age of information ecology can easily be affected by the consequences of information ecological imbalance. This imbalance may be triggered by maladjustment of the circulation in the system, by the abnormal flowing of some kinds of information, or the malfunction of some components in the chain of information flow. An information flow intervention approach, which imposes some control over information flow by means of semantic annotation, is proposed from the perspective of operationality and feasibility. The principal components in the proposed model are explained and the working principle of the model is explained. This research aims to realize ecological balance in a digital ecosystem by intervening in the flow of information, and consequently, providing some mechanism that will lead to the universal governance of the digital ecosystem.